2009
DOI: 10.1002/cbf.1619
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related effects of DHEA on peripheral markers of oxidative stress

Abstract: Ageing is an inevitable biological process characterized by a general decline in various physiological functions. DHEA and DHEAS levels are maximal between the second and third life decades, then start to decline 2% per year, leaving a residual of 10-20% of the peak production by the eighth decade. Erythrocytes are exposed to frequent oxidative stress due to the oxygen radicals continuously generated by haemoglobin auto-oxidation. We investigated DHEA chronic (10 mg/kg, subcutaneously, for 5 weeks) effects ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 45 publications
1
20
1
2
Order By: Relevance
“…Our results are consistent with Chen et al [18] who reported low levels of copper in serum and erythrocytes in diabetics in comparison to healthy subjects, but most of the studies on copper assays in diabetics have reported normal or increased copper levels [15,17,19]; however, this mol/dL [20]. Studies with an increase in the copper ion levels in patients with NIDDM might be attributed to hyperglycemia that may stimulate glycation and release of copper ions from copper-containing enzymes [11]; further studies are needed to verify this notion.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results are consistent with Chen et al [18] who reported low levels of copper in serum and erythrocytes in diabetics in comparison to healthy subjects, but most of the studies on copper assays in diabetics have reported normal or increased copper levels [15,17,19]; however, this mol/dL [20]. Studies with an increase in the copper ion levels in patients with NIDDM might be attributed to hyperglycemia that may stimulate glycation and release of copper ions from copper-containing enzymes [11]; further studies are needed to verify this notion.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, people who associate higher serum concentrations of DHEA with health probably should eat a diet adequate in copper [7] An advanced stage of diabetes is linked with an increase in oxidative substances [10]. DHEA has been considered as an antioxidant [11].…”
Section: Introductionmentioning
confidence: 99%
“…Our study indicates that aging aggravates I/R injury. Additionally, aging increased myocardial apoptosis and depressed post-ischemic cardiac functional recovery (Jacob et al 2010a;Shih et al 2011). Meanwhile, aging also increased in vivo ROS.…”
Section: Discussionmentioning
confidence: 99%
“…·O 2 − further dismutates to H 2 O 2 and ·OH, the latter being highly toxic to biological tissues, causative of significant myocardial necrosis and apoptosis. Several recent studies report that aging increases reactive oxygen species (ROS) (Adler et al 2003;Jacob et al 2010a;Jacob et al 2010b;Judge et al 2005). Leeuwenburgh and colleagues demonstrate increased mitochondrial ROS formation with aging (Judge et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It had reported that heart function atrophy is consistent evidence of aging (Jacob et al, 2010;Fan et al, 2011;Shih et al, 2011). HO-1 is an enzyme that catalyzes heme degradation, resulting in the production of biliverdin, iron, and carbon monoxide (Kikuchi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%